2000
DOI: 10.1646/0006-3606(2000)032[0642:dfgitp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Do Forest Gaps Influence the Population Structure and Species Composition of Mangrove Stands in Northern Australia?1

Abstract: Gap-phase regeneration of tropical mangroves was studied to test if there were significant environmental, structural, and floristic differences between canopy gaps and adjacent forests with intact canopies. Twenty-five canopy gaps in the low to mid intertidal zone were sampled at two study areas in northern Australia. Canopy gaps at the more equatorial study area were larger and had a higher surrounding canopy. Soil analyses showed that sediment texture exerts strong control on conductivity, pH, organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
(7 reference statements)
2
30
0
Order By: Relevance
“…light requirement) of canopy dominants may contribute to the maintenance of the present species composition in each vegetation zone. Clarke and Kerrigan (2000) proposed that gapphase regeneration of mangroves appears to follow a simple 'direct replacement' model in which a species population is replaced by members of the same species in forest gaps. This contrasts with tropical rain forests in which micro-succession, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…light requirement) of canopy dominants may contribute to the maintenance of the present species composition in each vegetation zone. Clarke and Kerrigan (2000) proposed that gapphase regeneration of mangroves appears to follow a simple 'direct replacement' model in which a species population is replaced by members of the same species in forest gaps. This contrasts with tropical rain forests in which micro-succession, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at both low and high salinity, seedling survivorship increased with light availability. A number of studies have found that in general there is higher mangrove seedling survivorship in gaps than non-gaps (Ball 2002;Clarke and Kerrigan 2000). Ball (2002) proposes two explanations: that there is more herbivory under closed canopies (e.g., Osborne and Smith 1990;Sousa et al 2003b;Lindquist and Carroll 2004); and that mortality in the shade could be due to below ground competition with surrounding adults (Passioura et al 1992).…”
Section: Whole-plant Responses To Light and Salinitymentioning
confidence: 99%
“…Firstly, some demographic studies have shown that densities of naturally occurring seedlings are greater beneath porous canopies than dense canopies (Ball 1980), and are greater in gaps than in closed forests (Sukardjo 1987). Other studies, however, found no differences in seedling densities between gaps and the surrounding forest, but reported more recruitment to the sapling stage in gaps (Jimenez 1988;Clarke and Allaway 1993;Clarke and Kerrigan 2000;Sherman et al 2000). Secondly, experimental studies have found that growth and survival of seedlings of several species are lower in the dense shade of closed canopies than in gaps (Smith 1987a, b;Clarke and Allaway 1993;Sherman et al 2000).…”
Section: Introductionmentioning
confidence: 99%